2015
DOI: 10.1111/padm.12225
|View full text |Cite
|
Sign up to set email alerts
|

Performance Feedback, Government Goal‐setting and Aspiration Level Adaptation: Evidence From Chinese Provinces

Abstract: Organizational goals shape performance feedback and have salient influences on strategic behaviours and outcomes. I develop a model of goal‐setting by combining performance gap and bureaucratic control theories. I predict that governments set goal levels historically in line with their past goal levels and attainment discrepancies, horizontally targeting the comparable peers' goal levels and performance gaps, and vertically aligning with the upper‐tier authorities' mandates. Using the data on annual economic g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(98 citation statements)
references
References 37 publications
3
95
0
Order By: Relevance
“…Scholars have studied the impacts of a wide range of variables, such as internal management and employee motivation, on organizational performance. However, the feedback effect of performance has only attracted some recent attention; scholars have studied performance feedback on variables such as budget changes, performance information use and goal setting (Nielsen ; Meier et al ; Ma ; Nicholson‐Crotty et al ; Flink ). We expand the research by studying performance feedback on employee turnover.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scholars have studied the impacts of a wide range of variables, such as internal management and employee motivation, on organizational performance. However, the feedback effect of performance has only attracted some recent attention; scholars have studied performance feedback on variables such as budget changes, performance information use and goal setting (Nielsen ; Meier et al ; Ma ; Nicholson‐Crotty et al ; Flink ). We expand the research by studying performance feedback on employee turnover.…”
Section: Discussionmentioning
confidence: 99%
“…scholars have studied performance feedback on variables such as budget changes, performance information use and goal setting (Nielsen 2014;Meier et al 2015;Ma 2016;Nicholson-Crotty et al 2017;Flink 2019). We expand the research by studying performance feedback on employee turnover.…”
Section: Discussionmentioning
confidence: 99%
“…Lü and Landry () argued that government officials tend to show their loyalty and yearn for promotion opportunities by purposefully elevating their performance ranking, and Jia, Kudamatsu, and Seim () found those well‐performing and high‐ranking officials have higher chances of promotion. Ma () indicated that in pursuit of promotion, the governors of provinces in China are under significant influence from the upper‐level authorities' mandates and peer provinces' goal levels. By analyzing China's urban environment statistics, Zheng, Kahn, Sun, and Danglun () contended that “pro‐green” incentives exerted on government officials could lead to environmental progress.…”
Section: Mandatory Target System Policy Feedback and The Official Rmentioning
confidence: 99%
“…Performance information can help the government identify performance deficits by means of comparison with its own past record as well as that of comparable peers. Such comparisons help to alert the management team to the need to catch up (Ma ). Performance information can also enable public managers to elicit and learn from benchmarks and best practices, and the knowledge and technical know‐how generated will help the organization narrow the gaps with the industrial leaders (Walker et al ).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%